Analisis Deiksis Dalam Cerita Pendek Rembulan di Mata Ibu dan Sepotong Cinta Dalam Diam Karya Asma Nadia - Sinta Ukhta Amalia; Laela Cahyani Rosyid; Sayidah Luthfi Nur Mukaromah; Fimahya Syafira Fiddinina; Adelia Nurul Fadilah; Asep Purwo Yudi Utomo; Yusro Edy Nugroho (Intellektika : Jurnal Ilmiah Mahasiswa, 2024)
Deixis is a pragmatic study that examines the relationship between language structure and the context of the situation in which it is used. The phenomenon of deixis can be found in everyday conversation in the form of verbal language as well as in literary works such as films or novels. In literary texts, deixis can pose an obstacle to understanding the text. The research entitled "Analysis of Deixis in the Short Stories 'Rembulan di Mata Ibu' and 'A Piece of Love in Silence' by Asma Nadia" aims to analyze the use of deixis in two short stories by Asma Nadia: "Rembulan di Mata Ibu" and "A Piece of Love in Silence." The method used in this research is a qualitative descriptive method. The data collection technique involved carefully reading and noting elements in the short stories. The data used consists of text fragments thought to contain deictic elements, including personal deixis, time deixis, place deixis, discourse deixis, and social deixis. Based on the results of data collection, 55 instances of personal deixis, 17 instances of time deixis, 11 instances of place deixis, 50 instances of discourse deixis, and 4 instances of social deixis were found. Thus, the total number of deictic instances is 137. It is hoped that this research will contribute significantly to the understanding of the use of deixis in literary works and help the public better comprehend the meanings and messages contained in such works.